The Prince of the Pin Elves - Sleight, Charles Lee; Sacker, Amy M. (Amy Maria), 1872-1965 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Prince of the Pin Elves" by Charles Lee Sleight is a children's fantasy novel written in the late 19th century. The story follows a young boy named Harry who, after discovering the secret world of the Pin Elves, has a series of magical adventures that lead him to uncover the peculiar duties and traditions of these tiny creatures. The book introduces enchanting themes of friendship, bravery, and the conflict between good and evil through lively characters and imaginative settings. At the start of the novel, Harry finds himself pondering the mystery of lost pins when he encounters an elf named Wamby who explains that they are the Pin Elves responsible for gathering lost pins. Wearing an elf's hat makes Harry invisible to others, allowing him to explore the enchanting world of the Pin Elves. As the narrative unfolds, Harry learns about the elves' king and their society while facing challenges that test his bravery. The opening sets the tone for an adventurous tale filled with vibrant illustrations and whimsical encounters, establishing Harry$1 (Bs character as curious and brave, making it an intriguing read for anyone who enjoys magical adventures. (This is an automatically generated summary.)s
Release date is 2023-09-27
Bob Taylor, Charlene Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Conduct of life -- Juvenile fiction; Children -- Conduct of life -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Princes -- Juvenile fiction; Magic -- Juvenile fiction; Gnomes -- Juvenile fiction; Battles -- Juvenile fiction; Elves -- Juvenile fiction